A Renewable Source of Bioenergy: Extraction, Spectral Characterization and Toxicological Studies with Microbial Screening on Indian Rubber (Hevea brasiliensis) Seed Oil - Arvind Narayan, Sundaram; Prabhu, Sivagnana; Shobana, Sutha; Dharmaraja, Jeyaprakash (Asian Journal of Chemistry, 2014)
The present study is carried out to find the extraction, physico-chemical analysis and toxicology with in vitro microbial screening characters of the Indian rubber seed oil. Vibrational studies of the oil exemplify the characteristic strong absorption at 1741 and 1461 cm–1 for –C=O and –C=C– groups respectively and did not give any idea about the presence of cyanide peak. Both the 1H NMR and 13C NMR spectral studies specify that the presence of triacylglycerol groups were saturated in addition to unsaturated. Determination of cyanide by means of colorimetric method was verified and there is no any absorption observed. This can be attributed that no hazardous linamarin were found in Indian rubber seed oil. Further, to estimate the potential of alternative hosts for oil production and influence of this oil with some common pathogenic microorganisms were also screened by well-diffusion techniques.